Elaeis guineensis oil palm - Rival, A. (CAB International, 2020)
This chapter focuses on the origin, geographical distribution, morphological, physiological and phenological characteristics, cultivation history, breeding, vegetative propagation methods and molecular genetics and genomics of oil palms (Elaeis guineensis). The importance of developing various genetic manipulation methods for the genetic improvement of oil palm germplasm is also discussed.